Work motivation of implementing nurses to improve the quality of health services - Rasi Rahagia; Fatimah Fatimah; Yoga Tri Wijayanti; Tunggul Sri Agus Setyaningsih; M. Khalid Fredy Saputra (Jurnal Ilmiah Kesehatan Sandi Husada, 2024)
Introduction: The motivation of the implementing nurse is essential to improving the quality of health services. Implementing nurses plays a vital role in providing quality services to patients. High work motivation is crucial in enhancing nurses' performance and commitment to providing the best care. Objective: Knowing the motivation behind implementing nurses can improve the quality of health services. Method: This research is quantitative, with a cross-sectional study design using a quantitative analytical approach. The number of samples was 81 people using total sampling. The research instrument used was a questionnaire with a Likert scale. The analysis method uses the Fisher's exact test. Results: Based on the results of the analysis, these employees have discipline that is still lacking in completing work, while of the 5 respondents who have low work motivation, three respondents (3.7%) have good performance. This is because employees have effectiveness, efficiency, authority, responsibility, discipline, and good work initiative. The statistical test results using Fisher's exact test obtained p = 0.009, smaller than a = 0.05 (p < 0.05), which means Ho is accepted and Ha is rejected. This suggests there is a meaningful relationship between work motivation and. Conclusion: The researchers found that the work motivation of implementing nurses can improve the quality of health services. Implementing nurses can enhance healthcare quality, build team spirit, and achieve organisational goals. These efforts help increase patient satisfaction and improve job satisfaction and nurses' well-being. Therefore, understanding and applying compelling work motivation is the key to improving the quality of health services.